Las Geórgicas como fuente indirecta en la Austriaca siue Naumachia de Francisco de Pedrosa. - Jiménez del Castillo, Juan Carlos (Myrtia, 2020)
In 1580, Francisco de Pedrosa, a Latin Grammar preceptor born in Madrid, finished a Lepantine epic in Guatemala: the unpublished Austriaca siue Naumachia. We analize a Protheus' prophecy scene based on Georgics book IV. We demonstrate that Pedrosa was inspired by this Vergilian episode and that this influence was driven by one of the main contemporary sources about Lepantine poetry: a book of poems collected by Pietro Gherardi, entitled In foedus et uictoriam contra Turcas iuxta sinum Corinthiacum Non. Octob. MDLXXI partam poemata uaria (Venice, 1572).